Analysis of the Implementation of the Accounting Application System for Line Ministry (SAKTI) in Government Financial Reporting at the Directorate General of State Asset Management, Ministry of Finance of the Republic of Indonesia - Indra Putra Perdana, Febry; Hardiyanto, Arief Tri; Endah Lestari, Retno Martanti (Journal of Social Transformation and Regional Development, 2023)
The purpose of this research is to analyze the obstacles and challenges in implementing the SAKTI Application in the financial management and financial reporting processes at the Directorate General of State Asset Management,  Ministry of Finance of Republic of Indonesia. The analysis covers various financial management processes, including payment and tax collection processes, as well as the manual journal and accrual journal formation processes in financial reporting. This study uses data obtained through direct research in the analysis unit, the workflow of reporting in the analysis unit, and literature review, employing a qualitative method, namely conducting interviews with authorized officials and employees in the analysis unit. The research findings indicate that in the implementation of SAKTI at the Directorate General of State Asset Management,  Ministry of Finance of Republic of Indonesia, there is still a need for other applications that are not integrated with SAKTI because SAKTI cannot fully identify third-party funds. To support the financial reporting process at the Directorate General of State Asset Management,  Ministry of Finance of Republic of Indonesia, as per the research results, it is found that the SAKTI application has not fully minimized the risk of errors in presenting accrual journal related to expenditure or rental income at the end of the year.